A generalized methodology for lithium-ion cells characterization and lumped electro-thermal modelling. (25th November 2022) - Broatch, Alberto; Olmeda, Pablo; Margot, Xandra; Agizza, Luca
Highlights: Electro-thermal modelling is needed to understand how lithium-ion cells generate heat. ECM need a wide testing with respect of temperature, SOC, current to map parameters. Extrapolation models can be coupled to experiments to get info outside test area. Electro-thermal lumped modelling can be easily integrated within BMS control strategy. The model can describe cell behavior without needing microscopic phenomena knowledge. Abstract: This paper deals with the experimental characterization and electro-thermal modelling of lithium-ion batteries. This aspect is of considerable importance to be able to understand the phenomena of heat generation and thermal behavior of a lithium-ion battery. Electrical parameters need to be characterized to properly estimate the electrical losses inside the battery and, thus, the total heat generation. The testing methodology is based on capacity test, open circuit voltage tests, and hybrid power pulse characterization tests. It highlights the dependency of each parameter on state of charge, current and temperature. A first order equivalent circuit model is used to simulate the electric behavior of the cell. Extrapolation physical models are used to accurately estimate capacity (Peukert model) and resistive parameters (Arrhenius model) for points outside the considered test matrix. The thermal behavior of the cell is modeled using a nodal network, assigning volume, heat capacity and heat generation to the nodes. The main output of the research is the development of a completely generalized methodology that can be adapted to any other chemistry, format, or capacity; furthermore, this methodology can be applied also in case of limited test matrix points, due to the implementation of extrapolation physical models for electrical parameters. The model is validated with a scaled real driving emission cycle. Finally, a case study for the fast charging of a battery module is presented, to highlight the great potential of the model, not only for on-line estimation, but also for off-line studies, being the charging operation one of the most critical from the thermal management point of view. From this analysis, it is found that a stand-alone cell can be charged for a longer time at 6C – a 5.42% more time -, with respect to the hottest cell in the considered battery module configuration.